Distinct SARS-CoV-2 specific NLRP3 and IL-1β responses in T cells of aging patients during acute COVID-19 infection - Mahalingam, Shanmuga Sundaram; Jayaraman, Sangeetha; Arunkumar, Adhvika; Dudley, Holly M.; Anthony, Donald D.; Shive, Carey L.; Jacobson, Jeffrey M.; Pandiyan, Pushpa (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes Coronavirus Disease 2019 (COVID-19) that presents with varied clinical manifestations ranging from asymptomatic or mild infections and pneumonia to severe cases associated with cytokine storm, acute respiratory distress syndrome (ARDS), and even death. The underlying mechanisms contributing to these differences are unclear, although exacerbated inflammatory sequelae resulting from infection have been implicated. While advanced aging is a known risk factor, the precise immune parameters that determine the outcome of SARS-CoV-2 infection in elderly individuals are not understood. Here, we found aging-associated (age ≥61) intrinsic changes in T cell responses when compared to those from individuals aged ≤ 60, even among COVID-positive patients with mild symptoms. Specifically, when stimulated with SARS-CoV-2 peptides in vitro, peripheral blood mononuclear cell (PBMC) CD4 + and CD8 + T cells from individuals aged ≥61 showed a diminished capacity to produce IFN-γ and IL-1β. Although they did not have severe disease, aged individuals also showed a higher frequency of PD-1 + cells and significantly diminished IFN-γ/PD-1 ratios among T lymphocytes upon SARS-CoV-2 peptide stimulation.Impaired T cell IL-1β expression coincided with reduced NLRP3 levels in T lymphocytes.However, the expression of these molecules was not affected in the monocytes of individuals aged ≥61. Together, these data reveal SARS-CoV-2-specific CD4 + and CD8 + T-cell intrinsic cytokine alterations in the individuals older than 61 and may provide new insights into dysregulated COVID-directed immune responses in the elderly.